Anatomical and physic - mechanical characterization of Narra (Pterocarpus indicus Willd.) branchwood collected in mount Makiling forest reserve, Laguna, Philippines - Mendoza, Rosalie C.; Daracan, Vivian C.; Manalo, Ronniel D.; Batallones, Chelle Hennessy R.; Jaurigue, Kisses G; Romano, Arlene D.; Abasolo, Willie P. (2019)
The properties of narra (Pterocarpus indicus Willd.) branchwood collected from Mount Makiling Forest Reserve (MMFR), Los Baños, Laguna, Philippines were studied. These branchwood properties were also compared with narra stemwood?s experimental and published properties. Core samples of stemwood were taken for anatomical characterization while branchwood samples were taken for anatomical (area percentage of fiber and parenchyma cells, fiber morphology, and computation of fiber indices), physical (moisture content, density, specific gravity, and shrinkage), and mechanical (static bending and compressive strength) analysis. Results showed that narra branchwood exhibits similar anatomical features to narra stemwood. Branchwood, however, has smaller pores, abundant inclusions, and less distinct storied arrangement of wood rays than stemwood. The area percentage of fiber cells is higher in stemwood while parenchyma percentage is higher in branchwood. Fiber dimensions appeared to be statistically the same for stemwood and branchwood, except for fiber length. Computed fiber indices of narra branchwood are also within the standard value ranges. In terms of mean density and specific gravity at 12% moisture content of the branchwood were 0.70 g/cm3 and 0.66, respectively. Mean tangential, radial, and longitudinal shrinkages were 3.59%, 3.37%, and 0.6%, respectively; while volumetric shrinkage was about 6.35%. The static bending properties of branchwood were not different from stemwood. The mean modulus of elasticity and modulus of rupture were 9.92 GPa and 96.59 MPa, respectively. On the other hand, the compressive strength parallel to the grain was lower at 32.64 MPa. Thus, narra branchwood may be used as a substitute for narra stemwood in various uses such as for high-grade furniture and cabinetry, musical instruments, pulp and paper, production of novelty items, and wood parquet. (Author's abstract)